The effect of tailoring pension information on navigation behaviour - Milena Dinkova; Sanne Elling; Adriaan Kalwij; Leo R. Lentz (Utrecht University, Utrecht University School of Economics (U.S.E.), 2019)
In this study, we analyzed whether tailoring the general structure of pension information on the basis of age affects the navigation behavior of participants. We conducted a randomized control experiment (RCE) among 8,563 employees of several firms, who were enrolled in a new company pension scheme. Participants were sent a generic invitation email to log into the digital pension environment (DPE) and were subsequently randomly assigned tailored versions of digital pension information, based on their age. The effect of tailoring on the participants' navigation behavior was analyzed on the time spent in the DPE and clicking on relevant pension information. Tailoring of the DPE was based on selected goals that were relevant for the separate age groups. Five percent of the participants logged into the DPE. We found no tailoring effect for young participants regarding the goal of knowing how their pension is arranged. Concerning the goal of knowing whether one is on track, tailoring the structure of the pension document was effective in distracting young participants from clicking on information not relevant to them and in motivating senior participants to click on relevant information. As for the goal of awareness of the choices available, we found that tailoring worked for senior participants as they clicked more on relevant pension information.
Keywords: C93; D83; D14; G41; J26; J32; 330; pension communication; pension information; retirement plans; tailoring; field experiment; financial decision making; navigation behavior